2020
DOI: 10.1088/1674-1056/ab7da9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal stabilities of Au@Ag core-shell nanoparticles and their arrays: A molecular dynamics simulation*

Abstract: Thermal stability of core-shell nanoparticles (CSNPs) is crucial to their fabrication processes, chemical and physical properties, and applications. Here we systematically investigate the structural and thermal stabilities of single Au@Ag CSNPs with different sizes and their arrays by means of all-atom molecular dynamics simulations. The formation energies of all Au@Ag CSNPs we reported are all negative, indicating that Au@Ag CSNPs are energetically favorable to be formed. For Au@Ag CSNPs with the same core si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Jia et al studied the structural and thermal stability of single Au@Ag nanoparticles with different sizes and their arrays by MD simulations. 79 They found that the pre-melting processes start from the surface region for both the single nanoparticles and their arrays. The melting points of Au@Ag core-shell bimetallic nanoparticles showed a feature of non-monotonicity with increasing core size at a fixed nanoparticle size.…”
Section: Coalescence Of Metal Nanoparticles With Different Elementsmentioning
confidence: 99%
“…Jia et al studied the structural and thermal stability of single Au@Ag nanoparticles with different sizes and their arrays by MD simulations. 79 They found that the pre-melting processes start from the surface region for both the single nanoparticles and their arrays. The melting points of Au@Ag core-shell bimetallic nanoparticles showed a feature of non-monotonicity with increasing core size at a fixed nanoparticle size.…”
Section: Coalescence Of Metal Nanoparticles With Different Elementsmentioning
confidence: 99%
“…Subsequently, Cu–Ag materials were heated from 300 to 1500 K in 1 ns (10 –9 s) with 1.2 K/ps. Finally, the open visualization tool (OVITO) was used to analyze the surface evolution of models during the sintering process …”
Section: Experimental Section and Simulation Detailsmentioning
confidence: 99%
“…Finally, the open visualization tool (OVITO) was used to analyze the surface evolution of models during the sintering process. 31 Characterization. X-ray diffraction (XRD) phase analysis of the Cu−Ag particles was recorded using a Bruker D8 ADVANCE diffractometer (Bruker Co., Ltd., Billerica, America) with Cu Kα as the radiation source.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[1,2] Considering the synergistic effects among metals, bimetallic nanoclusters are eliciting more research interest than monometallic ones. [3,4] Generally, the physical and chemical properties of binary metal clusters can be altered by varying their composition, atomic distribution, and structure, [5,6] enabling potential applications such as in catalysis fuel cells and hydrogen storage. [7] The structure types of bimetallic nanoalloys primarily include mixed structure, segregation structure, core-shell structure, and onion-like three-layer structure.…”
Section: Introductionmentioning
confidence: 99%